The Effect of Music on The International Architectural Design Process Output - Al-Ataabi, Mahdi Saleh; Alobaidy, Sana Ali Ibrahim (Iraqi Journal of Architecture and Planning, 2017)
Music has always had it’s generative role to build societies as one of modern culture basis . Arab Muslims had their own share of music industry as Al Farabi divided melodies to : delightful , imaginary & emotional , As Ibn Khadoon assured that civilizations fall as music falls eventually , some declared that music can transfer a still painting to a musical , motionable or aesthetic view of expression . As music’s role is increasing in fields specially architecture , thus , the main problem comes about musical architectural relationship , revealing the special case of somposing architectural texture musically , & the research problem exposed lack of knowledge about it & affection of music on architecture with outputs by subjecting architecture to music to promote outputs of design . This research aims to clarify that relationship & apply it on international buildings as the reseach concluded that sensual & moral indications can motivate designer’s imagination to design his outlines , aiming architectural use of music to produce intellectual joy ( objective ) reaching visible joy ( subjective ) by comprehensing an indicated concept based on previous experiments , as conclusions included that slow rhythm music leads to curved line and organic shapes & to straight lines & angles when listening to fast rhythem music